2022
DOI: 10.3390/ijerph191610314
|View full text |Cite
|
Sign up to set email alerts
|

Involvement, Perception, and Understanding as Determinants for Patient–Physician Relationship and Their Association with Adherence: A Questionnaire Survey among People Living with HIV and Antiretroviral Therapy in Austria

Abstract: Background: The relationship between patients and healthcare professionals (physicians) is the cornerstone of successful long-term antiretroviral therapy for people living with human immunodeficiency virus (HIV). Purpose: This study aimed to investigate the connection between involvement, perception, and understanding as the basis for the patient–physician relationship and drug adherence, measured as the probability of non-adherence. Methods: In an online survey, people with HIV were asked about their relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…A positive patient-physician relationship is an essential part in managing HIV because patients who form better relationships with their physicians have been shown to be more adherent to treatment, resulting in better long-term outcomes. 10 A systematic review by Taggart et al identified the benefits and limitations of using social media to communicate HIV prevention and treatment. 11 Social media users discussing HIV are diverse in terms of geographic locations, sexual orientations, ages, genders, races, and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…A positive patient-physician relationship is an essential part in managing HIV because patients who form better relationships with their physicians have been shown to be more adherent to treatment, resulting in better long-term outcomes. 10 A systematic review by Taggart et al identified the benefits and limitations of using social media to communicate HIV prevention and treatment. 11 Social media users discussing HIV are diverse in terms of geographic locations, sexual orientations, ages, genders, races, and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%